Southward key pathways of radioactive materials from the Fukushima Daiichi Nuclear Power Plant - Liu, Yihang; Zhou, Muping; Zhou, Feng; Meng, Qicheng; Ma, Xiao; Zhang, Qianjiang; Ye, Ruijie (Frontiers in Marine Science, 2024)
As a result of the nuclear accident triggered by the 2011 tsunami, the Fukushima Daiichi Nuclear Power Plant (FDNPP) in Japan experienced a release of radioactive materials, leading to varying degrees of nuclear contamination in the surrounding aquatic environments. This study focuses on the interannual and seasonal spatiotemporal distribution of radioactive substances in the surface ocean, considering the predominant accumulation of surface-level radioactive materials in the Kuroshio Extension (KE). The years 2015 and 2021 marked significant oscillatory phases of the KE's mean flow axis, moving southward and northward, respectively. Our observations revealed that radioactive particles released during summer predominantly drift eastward with the KE. In contrast, those released in winter demonstrate a marked southward trajectory. We also investigated the average time required for these substances to permeate critical neighboring marine regions. Our findings suggest that radioactive particles could reach the Luzon Strait in approximately 10 months, thereafter diverging northward along the Kuroshio and northwestward with the Kuroshio Branch Current.Notably, particles following the Kuroshio Branch Current could enter the South China Sea within a minimum of 13 months.This study examines the interannual and seasonal variations in the distribution of radioactive materials released from the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident in the surface layer of the Kuroshio Extension (KE). Focusing on the contrasting flow conditions in 2015 (southward) and 2021 (northward) -significant oscillatory phases of the KE's mean flow axis -the research analyzes the impact of seasonal variations on particle transport pathways. The findings reveal distinct seasonal patterns: summer releases primarily follow the eastward KE movement, while winter releases exhibit a southward trajectory. The study further quantifies the transport timescales, demonstrating that particles can reach the Luzon Strait within 10 months, subsequently diverging northward along the Kuroshio and northwestward along the Kuroshio Branch Current, potentially entering the South China Sea within 13 months. This research contributes valuable insights into the seasonal dynamics governing the dispersion and transport of Fukushima-derived radioisotopes in the surface ocean, highlighting the crucial role of the KE in influencing their trajectories.